Analisis Kausalitas Infrastruktur Telekomunikasi, Pertumbuhan Ekonomi dan Pembangunan Ekonomi di Indonesia - Annisa Khaira; Ariusni Ariusni (Universitas Negeri Padang, 2020)
This research explains about Analysis of causality beetwen Telecommunications Infrastructure, Economic Growth And Economic Development in Indonesia. This research uses a panel data start from 2012 – 2017,consisting of 33 province in Indonesia with proccessing method that use PVAR. Data was obtained from BPS report in every years. Reaserch results explain that (1) Telecommunications infrastructure has no causality influence one direction or two direction to economic to economic growth in Indonesia (2) Telecommunications infrastructure has causality influence one or two direction to economic to economic growth in Indonesia (3) Economic growth has no causality influence one direction or two direction economic development in Indonesia.